Language evolution and complexity considerations: The no half-Merge fallacy - Martins, Pedro Tiago; Boeckx, Cedric (PLOS Biology, 2019)
This Essay argues that the evolution of language cannot be as simple as prominent linguists Berwick and Chomsky have recently proposed, showing that the jump from the atomicity of Merge to a single-mutation scenario is not valid, and therefore cannot be used as justification for theory of language evolution along those lines.